2015
DOI: 10.1038/srep15213
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic sphingosine-1-phosphate pathway modulates neuronal autophagy

Abstract: Autophagy is an important homeostatic mechanism that eliminates long-lived proteins, protein aggregates and damaged organelles. Its dysregulation is involved in many neurodegenerative disorders. Autophagy is therefore a promising target for blunting neurodegeneration. We searched for novel autophagic pathways in primary neurons and identified the cytosolic sphingosine-1-phosphate (S1P) pathway as a regulator of neuronal autophagy. S1P, a bioactive lipid generated by sphingosine kinase 1 (SK1) in the cytoplasm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
103
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 51 publications
9
103
0
Order By: Relevance
“…S5D). This result is in line with a recent report that suggests that S1P is an initiator of autophagosome formation and SPL an inhibitor of autophagy in primary cells (45). Thus, ectopic expression of LpSpl can prevent autophagosome formation under nutrient limiting conditions.…”
Section: Resultssupporting
confidence: 92%
“…S5D). This result is in line with a recent report that suggests that S1P is an initiator of autophagosome formation and SPL an inhibitor of autophagy in primary cells (45). Thus, ectopic expression of LpSpl can prevent autophagosome formation under nutrient limiting conditions.…”
Section: Resultssupporting
confidence: 92%
“…In contrast, in neurons SGPL1 deficiency causes accumulation of S1P on the one hand and a drop in phosphatidylethanolamine on the other hand. The latter proved to block neuronal autophagy flux via an mTOR independent mechanism (Mitroi et al, ), whereas the former was shown to stimulate neuronal autophagy (Moruno Manchon et al, )…”
Section: Discussionmentioning
confidence: 99%
“…Although the modulation of autophagy by sphingolipids has been known for quite a while (Lavieu et al, ; Lepine et al, ), the number of studies that investigated this interrelationship in the brain wherein autophagy is indispensable to recycle aggregate prone proteins is rather scant (Moruno Manchon et al, ; van Echten‐Deckert & Alam, ). We have shown that neurons lacking SGPL1, the enzyme that catalyzes the irreversible cleavage of S1P into hexadecenal and ethanolamine phosphate accumulate S1P that exhibits a neurotoxic effect similar to that of Aβ.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, mTOR associates with sphingolipid-enriched vacuoles to that sphingolipids may regulate mTOR localization (Figure S6). Moreover, sphingolipids are established regulators of autophagy (Young et al, 2013), and the recruitment of SphK1 to endosomes, autophagosomes, and amphisomes has recently been linked to autophagosome biogenesis and degradation (Moruno Manchon et al, 2015; Manchon et al, 2016). Additionally, ceramide directly interacts with LC3-II to mediate cargo recruitment to autophagosomes for efficient degradation (Sentelle et al, 2012; Dany et al, 2016).…”
Section: Discussionmentioning
confidence: 99%